Large Animal Models of Huntington's Disease: What We Have Learned and Where We Need to Go Next - Howland, David; Ellederova, Zdenka; Aronin, Neil; Fernau, Deborah; Gallagher, Jill; Taylor, Amanda; Hennebold, Jon; Weiss, Alison R; Gray-Edwards, Heather; McBride, Jodi (Journal of Huntington's disease, 2020)
Genetically modified rodent models of Huntington's disease (HD) have been especially valuable to our understanding of HD pathology and the mechanisms by which the mutant HTT gene alters physiology. However, due to inherent differences in genetics, neuroanatomy, neurocircuitry and neurophysiology, animal models do not always faithfully or fully recapitulate human disease features or adequately predict a clinical response to treatment. Therefore, conducting translational studies of candidate HD therapeutics only in a single species (i.e. mouse disease models) may not be sufficient. Large animal models of HD have been shown to be valuable to the HD research community and the expectation is that the need for translational studies that span rodent and large animal models will grow. Here, we review the large animal models of HD that have been created to date, with specific commentary on differences between the models, the strengths and disadvantages of each, and how we can advance useful models to study disease pathophysiology, biomarker development and evaluation of promising therapeutics.
Keywords: prasata; Swine; modely nemocí na zvířatech; Huntingtonova nemoc; ovce; Swine, Miniature; Sheep; Huntington Disease; nonhuman primates; Animals, Genetically Modified; Animals; Minipigs; zvířata; Disease Models, Animal; Primates; primáti; sheep; therapeutics; geneticky modifikovaná zvířata; miniaturní prasata